Failure analysis of thin metal foils (Fracture and Structural Integrity, 2017)
The mechanical response and the failure mode of thin metal foils under tensile load has been analyzed supplementing the usual test records with full-field measurements performed by three-dimensional digital image correlation (3D DIC) techniques. The experiments have been simulated by finite element models formulated within a non-linear continuum framework. The study presented in this contribution concerns symmetrically pre-cracked aluminum samples. The wrinkling of the specimens during the test and the possible and alternative failure mechanisms are evidenced and discussed.
Keywords: Thin metal foils; Failure analysis; Digital image correlation; Numerical simulation